Continuous casting covering slag suitable for low-carbon alloy gear steel and method for reducing surface cracks of bloom low-carbon alloy gear steel
By optimizing the continuous casting protection slag composition and process parameters of low-carbon alloy gear steel, increasing the crystal precipitation temperature and thermal resistance of slag, improving the contact between the casting billet and the crystallizer, the cracks of low-carbon alloy gear steel during the solidification process of the crystallizer are solved. The problem of defects successfully reduces the surface crack defect rate.
Patent Information
- Application Number
- CN202411386403.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
Low-carbon alloy gear steel is prone to severe crack defects during the solidification process of the crystallizer, resulting in steel leakage accidents during production.
Chemical components are SiO2: 28-29.8%, Al2O3: 3.5-5.5%, CaO: 29-36.5%, MgO: 1.5-3.5%, Na2O: 4.0-6.5%, T.C: 12-17%, F: 2.0- 4.5%, Li2O: 0.20-0.35% continuous casting protective slag, alkalinity is 1.05-1.20, increase the crystal precipitation temperature and thermal resistance of the slag, optimize the vibration, cooling and electromagnetic stirring parameters of the crystallizer, and improve the casting and crystallizer Lubrication and heat transfer between.
The crack defect rate of the surface of the billet low-carbon alloy gear steel is significantly reduced, from the original 10% to within 1.0%, ensuring the quality and production safety of the casting billet.
Smart Images

Figure CN119237684A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and in particular to a continuous casting protective slag suitable for low-carbon alloy gear steel and a method for reducing surface cracks of large square billet low-carbon alloy gear steel. Background Art
[0002] Gear steel is one of the key materials with high requirements among special alloy steels used in automobiles, railways, ships, and engineering machinery. Among them, low-carbon alloy gear steel (mainly represented by 20MnCr5, 22CrMoH, 20CrMnTiH, etc.) is a carburizing steel with good performance, high hardenability, hard and wear-resistant surface and tough core after carburizing and quenching, high low-temperature impact toughness, medium weldability, and good machinability after normalizing. The gear steel ingots prepared at present have serious crack defects formed during the solidification process of the crystallizer. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a continuous casting protective slag suitable for low-carbon alloy gear steel and a method for reducing surface cracks of large square billet low-carbon alloy gear steel.
[0004] The present invention solves the technical problem by adopting the following technical solutions.
[0005] The present invention provides a continuous casting protection slag suitable for low-carbon alloy gear steel. The chemical composition of the continuous casting protection slag, measured by weight percentage, includes: SiO2: 28-29.8%, Al2O3: 3.5-5.5%, CaO: 29-36.5%, MgO: 1.5-3.5%, Na2O: 4.0-6.5%, TC: 12-17%, F: 2.0-4.5%, Li2O: 0.20-0.35%, and the rest are other inevitable impurities. The basicity of the continuous casting protection slag is 1.05-1.20.
[0006] The present invention also provides a method for reducing surface cracks in large square billet low-carbon alloy gear steel. The production process includes: converter smelting-LF refining-RH vacuum refining-large square billet continuous casting, wherein the above-mentioned continuous casting protective slag is used in the large square billet continuous casting process.
[0007] The present invention has the following beneficial effects:
[0008] The present invention provides a continuous casting protective slag suitable for low-carbon alloy gear steel and a method for reducing surface cracks of large square billet low-carbon alloy gear steel. The continuous casting protective slag suitable for low-carbon alloy gear steel provided by the present invention optimizes the protective slag composition, adopts a high basicity design concept, increases the crystal precipitation temperature, increases the crystallization tendency, increases the thermal resistance of the slag, controls the slow and uniform heat transfer of the billet, and improves the lubrication between the billet shell and the crystallizer to reduce the friction resistance between the billet shell and the crystallizer, thereby improving the surface crack defects of the billet. The surface crack defect rate of the low-carbon alloy gear steel produced by large square billet continuous casting is reduced from the original 10% to less than 1.0%. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0010] Figure 1 The surface condition of the casting blank prepared by the method provided in Example 1;
[0011] Figure 2 This is the surface condition of the ingot prepared by the method provided in Comparative Example 1. DETAILED DESCRIPTION
[0012] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0013] The following specifically describes a continuous casting protection slag suitable for low-carbon alloy gear steel and a method for reducing surface cracks in a large square billet low-carbon alloy gear steel provided in an embodiment of the present invention.
[0014] In the first aspect, an embodiment of the present invention provides a continuous casting protective slag suitable for low carbon alloy gear steel, the chemical composition of the continuous casting protective slag, calculated by weight percentage, includes: SiO2: 28~29.8%, Al2O3: 3.5~5.5%, CaO: 29~36.5%, MgO: 1.5~3.5%, Na2O: 4.0~6.5%, TC: 12~17%, F: 2.0~4.5%, Li2O: 0.20~0.35%, and the rest are other inevitable impurities. The basicity of the continuous casting protective slag is 1.05~1.20.
[0015] The composition and physical and chemical indicators of the existing low-carbon alloy gear steel protection slag are shown in the following table:
[0016] Element <![CDATA[SiO2]]> CaO MgO <![CDATA[Fe2O3]]> <![CDATA[Al2O3]]> R <![CDATA[R2O]]> content% 40.75 27.4 1.55 1.33 6.05 0.67 2.35 Element F C <![CDATA[H2O]]> Melting point Bulk density g / ml ViscosityPa.s content% 2.75 8.55 0.33 1195 0.68 1.56
[0017] As shown in the above table, the CaO and R of the existing protective slag are relatively low, the crystallization temperature of the protective slag is low, the precipitated crystals are relatively low, the heat transfer between the ingot and the crystallizer is too fast, and the ingot is easily separated from the crystallizer shell prematurely. The uneven heat transfer and the strong thermal sensitivity of the ingot itself lead to crack defects in the ingot during the solidification process of the crystallizer, which may cause steel leakage accidents in severe cases.
[0018] Since low-carbon alloy gear steel has a relatively high thermal contraction coefficient and a large shrinkage of the solidified billet shell, and contains high Cr, Mn, Mo and other alloy elements, the thermal conductivity is poor and the thermal sensitivity is strong. If the heat transfer between the billet and the crystallizer cannot be controlled during the continuous casting process, the billet heat transfer is too fast or uneven, resulting in the formation of crack defects on the billet surface. The protective slag for low-carbon alloy gear steel should slow down the heat transfer from the billet to the crystallizer, so that the billet shell transfers heat to the crystallizer evenly without generating surface defects. In order to achieve the purpose of uniform growth and slow down heat transfer, ensure the production of qualified low-carbon alloy gear steel billets. For the protective slag of low-carbon alloy gear steel, a protective slag system with large thermal resistance and high crystallization rate should be selected, because the protective slag has a high crystallization temperature, the precipitated crystals increase, and the thermal resistance of the slag increases, so that the purpose of slow cooling of the primary billet shell can be achieved.
[0019] Therefore, the present invention designs a continuous casting protective slag suitable for low-carbon alloy gear steel, adopts a high alkalinity design concept with alkalinity R of 1.05 to 1.20, increases the crystal precipitation temperature, increases the crystallization tendency, and increases the thermal resistance of the slag, so that the purpose of slow cooling of the primary billet shell can be achieved. At the same time, due to the increase in crystallization tendency and the increase in the thermal resistance of the slag, the friction assistance of the crystallizer will be increased, so reducing the Al2O3 in the protective slag can reduce the viscosity of the protective slag and improve the lubrication of the crystallizer; adding a certain amount of Li2O to the slag can slow down the denaturation of the protective slag, control the stability of the protective slag during use, and ensure the lubrication effect of the protective slag under high alkalinity. The above protective slag component design has a high crystallization temperature of the protective slag, increases the number of precipitated crystals, and increases the thermal resistance of the slag, so that the purpose of slow cooling of the primary billet shell can be achieved. At the same time, the components of the protective slag such as Al2O3, Na2O, and Li2O are optimized to control the slow and uniform heat transfer of the cast billet while improving the lubrication between the billet shell and the crystallizer and reducing the friction resistance between the billet shell and the crystallizer, thereby improving the surface crack defects of the cast billet.
[0020] In some optional embodiments, the continuous casting mold slag has a melting point of 1155° C. to 1220° C., a viscosity of 0.50 to 0.65 Pa.s, and a water content of ≤0.45%.
[0021] In a second aspect, an embodiment of the present invention provides a method for reducing surface cracks in large square billet low-carbon alloy gear steel, the production process comprising: converter smelting-LF refining-RH vacuum refining-large square billet continuous casting, wherein the above-mentioned continuous casting protective slag is used in the large square billet continuous casting process.
[0022] In some optional embodiments, the chemical composition of the low carbon alloy gear steel, measured in percentage by mass, includes: C: 0.15-0.25%, Si: 0.15-0.35%, Mn: 0.4-1.25%, Cr: 0.7-1.25%, Mo: 0.1-0.3%, Ti: 0.05-0.70%, P: ≤0.02%, S: ≤0.02%, and the remainder is iron and unavoidable impurities.
[0023] In some optional embodiments, in the converter smelting process, the C content of the converter endpoint is controlled to be 0.06-0.16%, and the carbon content is adjusted to 85-90% of the target carbon content during the steel tapping process.
[0024] In some optional embodiments, in the large square billet continuous casting process, a low superheat pouring method is used for pouring, wherein: the superheat of the first pouring furnace is controlled to be ≤40°C, and the superheat of the continuous pouring furnace is controlled to be ≤35°C, so as to increase the fine equiaxed crystal area of the casting billet and reduce component segregation.
[0025] In some optional embodiments, in the continuous casting process of large square billets, oxygen-free protection casting is performed throughout the entire process, the argon blowing pipeline is opened to blow argon into the tundish after the baking of the tundish is completed, a sealing ring and argon blowing are used between the long water inlet of the large ladle and the lower water inlet of the ladle for protection, and a magnesium covering agent is used for the tundish.
[0026] In some optional embodiments, in the large square billet continuous casting process, the crystallizer vibration frequency is controlled to be 208v, v is the production casting speed, the vibration stroke is 5-6mm, and the crystallizer electromagnetic stirring parameter is 100-300A / 2.5Hz; and the crystallizer cooling water adopts weak cooling control mode, and the hot and cold water flow is controlled to be 2600-2800L / min. The crystallizer electromagnetic stirring is in a unidirectional rotational motion in the large square billet. The rotation of the molten steel brings about changes in the heat flow, which has a certain effect on the cracks in the corner area of the billet. Appropriately reducing the size of the crystallizer electromagnetic stirring force is conducive to reducing the occurrence of cracks. Therefore, the crystallizer electromagnetic stirring parameters are controlled at 100-300A / 2.5Hz.
[0027] In some optional implementations, the method further includes controlling the pulling speed to be 0.60-0.70 m / min.
[0028] In some optional embodiments, the produced large square billet low-carbon alloy gear steel has a size of 425 mm*320 mm, and the proportion of surface crack defects is less than 1%.
[0029] The present invention will be further described below in conjunction with the embodiments.
[0030] Example 1
[0031] A method for reducing surface cracks of low-carbon alloy gear steel in large square billets, wherein the chemical composition of the low-carbon alloy gear steel, by mass percentage, includes: C: 0.15-0.25%, Si: 0.15-0.35%, Mn: 0.4-1.25%, Cr: 0.7-1.25%, Mo: 0.1-0.3%, Ti: 0.05-0.70%, P: ≤0.02%, S: ≤0.02%, and the remainder is iron and unavoidable impurities; the production process of the large square billet low-carbon alloy gear steel includes: converter smelting-LF refining-RH-vacuum refining-large square billet continuous casting. Among them:
[0032] The C content at the converter endpoint is controlled to be 0.06-0.16%, and the C content is adjusted to 85-90% of the target C content during the steel tapping process.
[0033] Continuous casting adopts large square billet continuous casting machine to produce billet section 425mm*320mm arc radius R14m full arc continuous casting machine
[0034] 1. Low superheat pouring: control the superheat of the first pouring furnace to ≤40℃, and control the superheat of the continuous pouring furnace to ≤35℃, so as to increase the fine equiaxed crystal area of the ingot and reduce the component segregation;
[0035] 2. The whole process of pouring is oxygen-free protection. After the tundish is baked, the argon blowing pipeline is opened to blow argon into the tundish. A sealing ring and argon blowing are used between the long water inlet of the large ladle and the lower water inlet of the ladle for protection. A magnesium covering agent is used for the tundish.
[0036] 3. The chemical composition of the continuous casting protection slag, calculated by weight percentage, includes: SiO2: 28-29.8%, Al2O3: 3.5-5.5%, CaO: 29-36.5%, MgO: 1.5-3.5%, Na2O: 4.0-6.5%, TC: 12-17%, F: 2.0-4.5%, Li2O: 0.20-0.35%, and the rest are other inevitable impurities. The basicity of the continuous casting protection slag is 1.05-1.2 (R=w(CaO) / w(SiO2)), the melting point is 1155℃~1220℃; the water content is ≤0.45%; and the viscosity is 0.50-0.65Pa.s.
[0037] 4. Continuous casting process parameters:
[0038] ① Process crystallizer vibration parameters: vibration frequency = 208v (v is the production drawing speed), vibration stroke is 5-6mm.
[0039] ②Pulling speed control: 0.60~0.70m / min.
[0040] ③ The cooling water of the crystallizer adopts weak cooling control mode to reduce the heat transfer rate of the casting. Flow control: 2600~2800L / min.
[0041] ④The electromagnetic stirring parameters of the crystallizer are controlled at 100~300A / 2.5Hz.
[0042] See the appearance photo of the ingot obtained by the solution provided in Example 1. Figure 1 The left and right pictures are products of the same batch with different numbers. It can be seen that there are no obvious defects on the surface of the ingot and the crack incidence rate is less than 1%.
[0043] Comparative Example 1 (Original Process)
[0044] There is no control requirement for controlling the converter endpoint C, and the C content during the steelmaking process is adjusted to 85-90% of the target C content.
[0045] The continuous casting adopts a large square billet continuous casting machine to produce billet cross-section 425mm*320mm arc radius R14m full arc continuous casting machine.
[0046] 1. Low superheat pouring: control the superheat of the first pouring furnace to ≤40℃, and control the superheat of the continuous pouring furnace to ≤35℃, so as to increase the fine equiaxed crystal area of the ingot and reduce the component segregation;
[0047] 2. The whole process of pouring is oxygen-free protection. After the tundish is baked, the argon blowing pipeline is opened to blow argon into the tundish. A sealing ring and argon blowing are used between the long water inlet of the large ladle and the lower water inlet of the ladle for protection. A magnesium covering agent is used for the tundish.
[0048] 3. The chemical composition of the continuous casting mold slag is shown in the following table in terms of weight percentage, composition and physical and chemical indicators:
[0049] Element <![CDATA[SiO2]]> CaO MgO <![CDATA[Fe2O3]]> <![CDATA[Al2O3]]> R <![CDATA[R2O]]> content% 40.75 27.4 1.55 1.33 6.05 0.67 2.35 Element F C <![CDATA[H2O]]> Melting point Bulk density g / ml ViscosityPa.s content% 2.75 8.55 0.33 1195 0.68 1.56
[0050] Low basicity mold slag reduces the crystal precipitation temperature, crystallization tendency, and thermal resistance of slag. It is beneficial to the rapid cooling of the ingot and increases the thickness of the ingot. However, the rapid heat transfer leads to greater stress in the ingot, increasing the probability of cracks on the surface of the ingot. In addition, the higher Al2O3 in the mold slag increases the viscosity of the mold slag and increases the friction between the ingot and the crystallizer, which further increases the probability of cracks on the surface of the ingot.
[0051] 4. Continuous casting process parameters:
[0052] ① Process crystallizer vibration parameters: vibration frequency = 188v (v is the production casting speed), vibration stroke is 5-6mm. The consumption of protective slag is a decreasing function with the vibration frequency. The smaller the vibration frequency, the greater the slag consumption. The greater the slag consumption, the faster the heat transfer, resulting in increased stress in the casting.
[0053] ②Pulling speed control: 0.60~0.70m / min.
[0054] ③ The cooling water of the crystallizer adopts the strong cooling control mode. Flow control: 3400~3600L / min. The increase of the crystallizer water flow rate accelerates the heat transfer of the casting, which is easy to cause crack defects in the casting.
[0055] ④ The electromagnetic stirring parameters of the crystallizer are controlled at 600-710A / 2.5Hz. The rotation of molten steel brings about changes in heat flow, which has a certain influence on the cracks in the corner area of the ingot. A larger electromagnetic stirring intensity increases the cracks in the corner area.
[0056] See the appearance photo of the ingot obtained by the solution provided in Comparative Example 1. Figure 2 The left and right pictures are products of the same batch with different numbers. It can be seen that the surface of the ingot has serious crack defects, and the crack incidence rate is as high as 10%.
[0057] Comparative Example 2
[0058] The steps are similar to those in Example 1, except that the basicity of the crystallizer protective slag during the preparation process is 0.70 (R = w(CaO) / w(SiO2)), and the viscosity is 1.35 Pa.s. Low-basicity protective slag reduces the crystal precipitation temperature, reduces the crystallization tendency, and reduces the thermal resistance of the slag. It is beneficial to the rapid cooling of the ingot and increases the thickness of the ingot. But at the same time, the rapid transfer of heat causes greater stress to form on the ingot, increasing the probability of crack formation on the surface of the ingot. The viscosity of the protective slag increases the friction between the ingot and the crystallizer, further increasing the probability of crack formation on the surface of the ingot. However, optimization of vibration and water volume in the crystallizer can improve cracks in the ingot to a certain extent.
[0059] The result was that crack defects appeared on the surface of some ingots, and the crack incidence rate was 6.0%.
[0060] Comparative Example 3
[0061] The steps are similar to those in Example 4, except that the cold water flow rate of the crystallizer during the preparation process is 3600 L / min. The optimization of the mold slag composition and physical and chemical performance indicators slows down the heat transfer between the ingot and the crystallizer and improves the friction resistance between the ingot and the crystallizer, which is beneficial to improve the cracks in the ingot. However, the increase in the amount of water in the crystallizer also accelerates the heat transfer between the ingot and the crystallizer, increases the stress of the ingot, and increases the probability of crack defects in the ingot.
[0062] The result was that crack defects appeared on the surface of some ingots, and the crack incidence rate was 3.0%.
[0063] Comparative Example 4
[0064] The steps are similar to those in Example 1, except that the vibration frequency of the process crystallizer during the preparation process = 180v (v is the production pulling speed), and the vibration stroke is 5-6mm. The consumption of protective slag and the vibration frequency are decreasing functions. The smaller the vibration frequency, the greater the slag consumption. The large slag consumption accelerates the heat transfer, resulting in increased stress in the ingot and an increased crack tendency. The optimization of the protective slag composition and physical and chemical performance indicators slows down the heat transfer between the ingot and the crystallizer and improves the friction resistance between the ingot and the crystallizer, which is beneficial to improving the cracks in the ingot. However, the optimization of the water volume in the crystallizer also slows down the heat transfer between the ingot and the crystallizer, reducing the probability of crack defects in the ingot.
[0065] The result was that crack defects appeared on the surface of some ingots, and the crack incidence rate was 2.5%.
[0066] By analyzing the results of the embodiments of the present invention and the comparative examples, it can be seen that the embodiments of the present invention provide a continuous casting protective slag suitable for low-carbon alloy gear steel and a method for reducing surface cracks in large square billet low-carbon alloy gear steel. In the present invention, by optimizing the protective slag composition and adopting a high-alkalinity design concept, the crystal precipitation temperature is increased, the crystallization tendency is increased, and the thermal resistance of the slag is increased, so that the purpose of slow cooling of the primary billet shell can be achieved. In addition, the vibration, cooling, and electromagnetic stirring tooling equipment and parameters of the continuous casting crystallizer are optimized to further improve the crack defects of low-carbon alloy gear steel. The surface crack defect rate of low-carbon alloy gear steel produced by large square billet continuous casting is reduced from the original 10% to less than 1.0%.
[0067] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A continuous casting mold slag suitable for low-carbon alloy gear steel, characterized in that: The chemical composition of the continuous casting protection slag, calculated by weight percentage, includes: SiO2: 28-29.8%, Al2O3: 3.5-5.5%, CaO: 29-36.5%, MgO: 1.5-3.5%, Na2O: 4.0-6.5%, TC: 12-17%, F: 2.0-4.5%, Li2O: 0.20-0.35%, and the rest are other inevitable impurities. The basicity of the continuous casting protection slag is 1.05-1.
20.
2. The continuous casting mold slag according to claim 1, characterized in that: The continuous casting protection slag has a melting point of 1155° C. to 1220° C., a viscosity of 0.50 to 0.65 Pa.s, and a water content of ≤0.45%.
3. A method for reducing surface cracks in bloom low-carbon alloy gear steel, characterized in that: The production process comprises: converter smelting - LF refining - RH vacuum refining - large square billet continuous casting, wherein the continuous casting protection slag according to claim 1 or 2 is used in the large square billet continuous casting process.
4. The method according to claim 3, characterized in that: The chemical composition of the low carbon alloy gear steel, measured by mass percentage, includes: C: 0.15-0.25%, Si: 0.15-0.35%, Mn: 0.4-1.25%, Cr: 0.7-1.25%, Mo: 0.1-0.3%, Ti: 0.05-0.70%, P: ≤0.02%, S: ≤0.02%, and the remainder is iron and unavoidable impurities.
5. The method according to claim 3, characterized in that: In the converter smelting process, the C content at the converter endpoint is controlled to be 0.06-0.16%, and the carbon content is adjusted to 85-90% of the target carbon content during the steel tapping process.
6. The method according to claim 3, characterized in that In the continuous casting process of large square billets, a low superheat pouring method is used for pouring, wherein the superheat of the first pouring furnace is controlled to be ≤40°C, and the superheat of the continuous pouring furnace is ≤35°C, so as to increase the fine equiaxed crystal area of the billet and reduce component segregation.
7. The method according to claim 3, characterized in that In the continuous casting process of large square billets, oxygen-free protection is used for pouring throughout the whole process. After the baking of the tundish is completed, the argon blowing pipeline is opened to blow argon into the tundish. A sealing ring and argon blowing are used for protection between the long water inlet of the large ladle and the lower water inlet of the ladle. A magnesium covering agent is used for the tundish.
8. The method according to claim 3, characterized in that In the large square billet continuous casting process, the vibration frequency of the crystallizer is controlled to 208v, v is the production casting speed, the vibration stroke is 5-6mm, the electromagnetic stirring parameter of the crystallizer is 100-300A / 2.5Hz; and the cooling water of the crystallizer adopts weak cooling control mode, and the hot and cold water flow rate is controlled to 2600-2800L / min.
9. The method according to claim 8, characterized in that Also includes: Control the pulling speed to 0.60~0.70m / min.
10. The method according to any one of claims 3 to 9, characterized in that: The size of the produced large square billet low-carbon alloy gear steel is 425mm*320mm, and the proportion of surface crack defects is less than 1%.
